Letters by and to Religious Women in Light of the Rule, Single Letters, and Letter Collections: A Research Survey - Signori, Gabriela (Journal of Medieval Monastic Studies, 2017)
Abstract Of the numerous and in part excellent case studies on letters by and to religious women - the focus of this article - few have been comparative, only ever focusing on the analysis of singular letters or letter collections. In the following, I endeavour to systematize the results gleaned from such case studies. My research survey zooms in on two long-prevalent types of monastic letters: the pastoral or admonitory letter and the epistola familiaris, to which the ‘mystical letter’ in Wilhelm Oehl’s terms can be added. My argument will be introduced by an overview of the stipulations of rule texts, substantiating why the pastoral letter dominates in this context and why most early and high medieval letters from and to women were authored by abbesses. This changed in the fifteenth century, when letter writing was elevated to a ubiquitously mastered cultural technique.